A Subgroup Reanalysis of the Efficacy of Bufei Huoxue Capsules in Patients With “Long‐Covid‐19” - Chi Hou; Yue Xing; Yuqin Chen; Tingping Wang; Jingjing Qi; Xiaoqing Jia; Xiansheng Zeng; Jianling Bai; Wenju Lu; Yu Deng; Bihua Zhong; Yongxia Lei; et al. (Pulmonary Circulation, 2025)
ABSTRACT Bufei huoxue capsules (BFHX), manufactured products of traditional Chinese medicine, have demonstrated anti‐inflammatory properties and efficacy against chronic pulmonary diseases and COVID‐19. This study was designed to further determine the clinical efficacy of BFHX in diverse patient subgroups during the convalescent phase of COVID‐19, extending upon previously reported findings from a multicenter randomized controlled trial. Patients who had clinically recovered from COVID‐19 were blindly assigned to BFHX or placebo groups. All enrolled patients underwent chest computed tomography (CT) imaging, 6‐min walking distance (6MWD) test, and fatigue assessment inventory (FAI) at monthly follow‐up for 3 months. A post hoc subgroup reanalysis was performed on subgroups of sex, age, severity of acute illness, and positive/negative IgG antibody against S antigen variants. A total of 129 patients were enrolled in BFHX (N = 64) and placebo groups (N = 65). The 6MWD and FAI scores were more significantly improved in females and mild patients than in males and severe patients after BFHX treatment. Lung CT image evaluated by the change in whole lung volume and mean CT value showed that the patients below 60 years gained more therapeutic effects after 3 months of BFHX treatment (p = 0.0008; p = 0.017; p = 0.0313, respectively). The subgroup reanalysis implies that the therapeutic effectiveness of BFHX in managing COVID‐19 convalescence could potentially be influenced by factors including gender, age, and disease severity. Trial registration: This study was registered with the China Clinical Trial Registration Center (registration number: ChiCTR2000032573).